2018
DOI: 10.1161/circheartfailure.117.004665
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Circulatory Support Device Utilization and Heart Transplant Waitlist Outcomes in Patients With Restrictive and Hypertrophic Cardiomyopathy

Abstract: Patients with RCM/HCM are less likely to receive MCSD but have similar waitlist mortality and slightly higher incidence of transplantation compared with other patients. The United Network for Organ Sharing RCM/HCM risk model can help identify patients who are at high risk for clinical deterioration and in need of expedited heart transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…End‐stage heart failure (HF) patients with the underlying diagnosis of restrictive (RCM) and hypertrophic cardiomyopathy (HCM) represent approximately 5% of patients listed for heart transplantation (HT) 1 . These patients historically have a higher mortality on the HT list and were more often delisted due to worsening clinical status when compared with other cardiomyopathies 2–4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…End‐stage heart failure (HF) patients with the underlying diagnosis of restrictive (RCM) and hypertrophic cardiomyopathy (HCM) represent approximately 5% of patients listed for heart transplantation (HT) 1 . These patients historically have a higher mortality on the HT list and were more often delisted due to worsening clinical status when compared with other cardiomyopathies 2–4 .…”
Section: Introductionmentioning
confidence: 99%
“…These patients historically have a higher mortality on the HT list and were more often delisted due to worsening clinical status when compared with other cardiomyopathies 2–4 . This patient population has limited benefit from durable mechanical circulatory support (MCS) devices and they are therefore infrequently used, 1 with a reported 1‐year survival of 64% after left ventricular assist device (LVAD) implantation 5 compared to 82% survival for an unselected LVAD population 6 . Survival after HT for RCM/HCM patients, however, is comparable to overall post‐HT survival, and waitlist registration for RCM/HCM indications has been increasing significantly relative to other cardiomyopathies 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the increased waitlist mortality and delisting observed among INTERMACS profile I-II patients aligns with previous studies that have demonstrated an association between hemodynamic deterioration requiring inotrope use and mortality on the HTx waitlist. 17,18 Recent work has also indicated that the use of VAD as BTT is associated with a lower waitlist mortality in critically decompensated heart transplant candidates. 19 This fits with the observation in the current study that VAD implantation significantly improves waitlist survival in patients profiled as INTERMACS I-II.…”
Section: Relation To Previous Workmentioning
confidence: 99%
“…Status 2 patients were those on oral medications and considered low urgency for HT. This 3‐tier system did not adequately account for the needs of patients who are often less tolerant of inotropes or those with cardiomyopathies structurally incompatible with left ventricular assist devices or other MCS, 3–7 such as patients with infiltrative, hypertrophic, and restrictive cardiomyopathies. With this allocation system, status exceptions were needed to upgrade listing status for these individuals, in the event of clinical deterioration.…”
Section: Introductionmentioning
confidence: 99%